Visual and Participatory Educational Innovation to Promote Immunization Awareness in Nibong Village - Yuliana, Yuliana; Idawati; Fauza, Rizka; Faridah; Harahap, Meliani Sukmadewi (Lembaga Riset dan Inovasi Masyarakat Madani, 2025)
Low awareness and coverage of complete basic immunization among under-five children in Nibong Village remains a pressing public health issue. This study evaluated a community-based, visual–participatory education program designed to improve immunization awareness among mothers/caregivers. Over four weeks, 35 caregivers attended interactive counseling supported by co-created visual materials (leaflets, posters, participatory aids) and cadre training. Data were collected using a brief pre–post questionnaire (knowledge, myths/beliefs, intention to attend posyandu) and qualitative observations. Descriptive analysis showed an increase in maternal knowledge from 28.6% to 71.4% and higher engagement with immunization services. Reported completion of basic immunization increased from 14% to 86% (self-reported; verification recommended via child health cards or posyandu records). Qualitative insights indicated that locally adapted visuals, cadre facilitation, and familiar language enhanced comprehension and trust. A visual–participatory, community-based approach is feasible and promising for strengthening immunization awareness and participation. Wider adoption should include objective verification of coverage and longer follow-up.